2018
DOI: 10.1002/jso.25298
|View full text |Cite
|
Sign up to set email alerts
|

Updates in adjuvant systemic therapy for melanoma

Abstract: There has been a rapid increase in adjuvant therapies approved for treatment following surgical resection of stage III/IV melanoma. We review current indications for adjuvant therapy, which currently includes a heterogenous group of Stage III and IV melanoma patients. We describe several pivotal clinical trials of systemic immune therapies, targeted immune therapies, and adjuvant vaccine strategies. Finally, we discuss the evidence for selecting the most appropriate treatment regimen(s) for the individual pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
(176 reference statements)
1
28
0
1
Order By: Relevance
“…Dacarbazine (DTIC) has been recognized as the only chemotherapy drug approved by the Food and Drug Administration (FDA) for progressive MM since 1972 [18]. In recent years, with the development of genetic testing technology, exploration of immune-and targeted-therapy, immune therapy has been gradually used for these patients [20,21]. Clinical studies showed that the skin melanoma with more mutated BRAF gene mutation and AM accounted for only 17% of BRAF gene mutations, and KIT gene mutation was 15% ~ 40% (3,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dacarbazine (DTIC) has been recognized as the only chemotherapy drug approved by the Food and Drug Administration (FDA) for progressive MM since 1972 [18]. In recent years, with the development of genetic testing technology, exploration of immune-and targeted-therapy, immune therapy has been gradually used for these patients [20,21]. Clinical studies showed that the skin melanoma with more mutated BRAF gene mutation and AM accounted for only 17% of BRAF gene mutations, and KIT gene mutation was 15% ~ 40% (3,22).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed that the skin melanoma with more mutated BRAF gene mutation and AM accounted for only 17% of BRAF gene mutations, and KIT gene mutation was 15% ~ 40% (3,22). Additionally, the efficacy of nivolumab in melanoma has been recognized [21]. However, there is still lack of objective data to evaluate AM patients in China, thus, the efficacy of targeted therapy and immunotherapy needs to be studied for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ICB and BRAF/MEKi have demonstrated significant survival benefits in stage III melanoma. [22][23][24][25] .Neoadjuvant sequencing of these novel therapies is feasible for clinically evident disease, and, in a subset of patients, can result in a complete pathologic response. [26][27][28] As the trend continues toward less extensive locoregional surgery for melanoma, it must be balanced with a better understanding of risk patterns for recurrence in the context of novel systemic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite much research, the mechanisms of the occurrence and development of melanoma remains unclear. Surgery, radiotherapy and chemotherapy have long been the main methods for melanoma treatment, but these methods also have some problems, such as severe trauma, obvious side effects and low patient tolerance [31]. With the recent process in treatment, immune therapies and targeted therapies are two main treatment approaches for patients with advanced melanoma, but both still have limitations, and not all patients experience sustained responses [32].…”
Section: Discussionmentioning
confidence: 99%